(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Interest in obtaining a more accurate snapshot of the territory is increasingly relevant in most geographic studies. This proposal is based on the stakeholder analysis approach and the governance model approach to analysing any topic with a geographical profile or interest from an educational and methodological point of view. The selection of those approaches and the application of some related techniques have been used to generate a new tool for identifying and characterizing the key stakeholders in order to understand their behaviour and its influence or power on decision-making processes.Â This methodology can be used by educational members and geographers as a working basis to analyse an exchange social-learning from confronted interests.